Commentary and tradition : Aristotelianism, Platonism, and post-Hellenistic philosophy - Donini, Pierluigi, 1940- (Commentaria in Aristotelem Graeca et Byzantina. Quellen und Studien, 2011)
The volume collects the most important papers Pierluigi Donini wrote in the last three decades with the aim of promoting a better assessment of post-hellenistic philosophy. By focusing on the mutual confrontation with Plato's and Aristotle's texts for the development of both Aristotelianism and Platonism, Donini's papers provide the readers with an overall account of the philosophy of the commentators and argue for its importance for the history of the European thought.